2009
DOI: 10.1152/ajpregu.90451.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to oxidative stress and different patterns of senescence in human peritoneal mesothelial cell strains

Abstract: Ksiazek K, Mikula-Pietrasik J, Olijslagers S, Jörres A, von Zglinicki T, Witowski J. Vulnerability to oxidative stress and different patterns of senescence in human peritoneal mesothelial cell strains. Am J Physiol Regul Integr Comp Physiol 296: R374 -R382, 2009. First published November 26, 2008 doi:10.1152/ajpregu.90451.2008.-Both the ascites fluid-derived mesothelial cell line LP-9 and primary cultures of human omentum-derived mesothelial cells (HOMCs) are commonly used in experimental studies. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…SASP components contributing to relapse and aggressive cancer occurrence 22 include: interleukins 6 and 8 (IL-6, IL-8) 23 ; amphiregulin (AREG) and growth-related oncogene (GRO) α 24, 25 , VEGF 26, 27 or matrix metalloproteinases (MMPs) 25, 28, 29 . SASP has recently been linked to immune surveillance of damaged normal and tumor cells 3032 .…”
Section: Introductionmentioning
confidence: 99%
“…SASP components contributing to relapse and aggressive cancer occurrence 22 include: interleukins 6 and 8 (IL-6, IL-8) 23 ; amphiregulin (AREG) and growth-related oncogene (GRO) α 24, 25 , VEGF 26, 27 or matrix metalloproteinases (MMPs) 25, 28, 29 . SASP has recently been linked to immune surveillance of damaged normal and tumor cells 3032 .…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards they were harvested by trypsinization, counted again and subjected to fluorescence analysis based on measurement of the rate of conversion of 4-methylumbelliferyl-β-D-galactopyranose (MUG) to 4-methylumbelliferone (4-MU), as described by Gary and Kindell (2005). The results obtained using the fluorescence method were normalized per cell autofluorescence level, which could be related to the presence and senescence-associated increase in the lipofuscin content (Ksiazek et al 2009b). …”
Section: Methodsmentioning
confidence: 99%
“…Several processes have been identified that cause or are associated with cellular senescence, all of which also increase with age ( Figure 3). Senescence-causing inducers include repeated cell division and strong mitogenic signals, telomere shortening, DNA damage and mutations, protein aggregation, and increased ROS (46,(56)(57)(58)(59)(60). These insults activate the p53 and p16 INK4a tumor suppressor pathways and potentially other pathways that initiate a senescence response.…”
Section: Cellular Senescencementioning
confidence: 99%